A STUDY ON INFORMATION GAP ACTIVITIES IMPLEMENTATION IN TEACHING SPEAKING SKILLS FOR FIRST YEAR STUDENTS AT FELTE, ULIS, VNU - Trần, Thị Hồng (ĐHQGHN - Đại học Ngoại ngữ, 2021)
Of four skills taught in tertiary education, speaking has gained its prominent position due to its good response to society‟s demand. Under the influence of communicative language teaching (CLT), out-dated teaching methods in forms of drills and memorization have been shifted to communicative approach with the exploitation of information gap activities. As a result, information gap activities (IGA) have been widely used at language spoken institutions like ULIS, VNU. The researcher carried out a study titled “A study on information gap activities implementation in teaching speaking skills for first year students at FELTE, ULIS, VNU”. The aim of this study was to investigate the types of IGA mostly used, the strategies applied during IGA and the obstacles as perceived by teachers and students at Division I. To fulfill these objectives, the researcher employed both qualitative and quantitative methods based on the theoretical background. Thanks to participants‟ cooperation and the utility of data collection instruments, including questionnaires, indepth interviews and classroom observations, three research questions were fully answered. Results showed that exchanging personal information was preferred by teachers owing to its simplicity and flexibility. Moreover, forming groups according to proximate seat positions, delivering instructions by “say-do-check” and “step-by-step” techniques, actively monitoring the class and giving feedback at the end of the activity were more frequently used than other techniques. In addition, the research also displayed the obstacles faced by teachers and students related to students‟ levels and class layout. Based on these findings, some implications were made for a better exploitation of IGA in teaching speaking. The study was expected to benefit not only teachers and students at Division I but also other researchers interested in this field